(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: The experiment was conducted to determine the effect of dietary energy and protein level growth performances of selected indigenous Ethiopian sheep breeds. Materials and Methods: Fifty intact ram lambs, 25 from each breed with 12 months of age and a mean initial body weight (IBW) of 19.31 ± 1.7 kg, were employed for this experiment. Animals were distributed randomly into five dietary treatments, i.e., minimum Energy and Protein (mEmP), medium energy and protein (MEMP), medium Energy and high Protein (MEHP), high energy and medium protein (HEMP), and high Energy and high Protein (HEHP) diets in randomized complete block design with 2 * 5 factorial arrangements. The minimum, medium, and high energy diets were 2.388, 2.866, and 3.344 Mcal/kg dry matter (DM) with the corresponding 10%, 16%, and 20% crude protein (CP) diets, respectively. The diets were formulated in a total mixed ration from wheat bran (WB), maize grain, peanut cake, and pasture hay feed ingredients. Diet offer was at the rate of 3% of lambs’ live weight and revised biweekly as per the attained body weight changes. Digestibility trial was conducted for 7 days of actual fecal data collection, followed by 90 days of feeding trial. Results: The animals fed on the MEHP diet had a maximum DM and nutrient intakes (CP and organic matter) and the best final body weight (FBW), total gain, gain rate, average daily gains, and feed conversion efficiency (31.3, 12.9 kg, 41.2%, 143.3 gm, and 23.13, respectively), followed by HEMP, HEHP, MEMP, and mEmP diets. Digestibility of DM and nutrients linearly followed similar trends (p < 0.01). Hararghe sheep was heavier (p < 0.01) by 4.3 and 3.1 kg in its FBW and total gain and more efficient in nutrients utilization (22.57 vs. 18.18) as compared to Afar sheep (AS). Conclusion: It is concluded that MEHP and MEMP are superior and optimum diets for sheep breeds, and Hararghe sheep is carried out better than AS in most growth performance parameters. J. Adv. Vet. Anim. Res., 8(2): 185-194, June 2021